FISHERIES COOPERATIVE FINANCIAL REPORT BINA USAHA MAJU GAMPUNG BLANG NALEUNG MAMEH KECAMATAN MUARA SATU KOTA LHOKSEUMAWE - Yulia Putri, Riska; Riska Ayunda, Tia; Waznah, Waznah; Parida, Desi; Saharuddin, Saharuddin (RADJA PUBLIKA, 2023)
Cooperatives as an economic system play a very important role in increasing the income and income distribution of its members. Cooperatives are companies that must be able to provide economic services to their members and the surrounding community. Cooperative performance can be seen from the financial reports. This study aims to determine the finance of Fishery Cooperatives for advanced business development. This can be obtained by analyzing the financial statements of cooperatives. This study used several techniques, namely interviews, questionnaires and observation. The location is in the village of Blang Naleung Mameh, Muara sub-district, North Aceh district. The results of this study show that the results of the 2018 financial statements have decreased.